APLIKASI PENGELOLAAN INVENTARIS BARANG DI SMK NEGERI 1 PLAMPANG BERBASIS WEB - Yudi Mulyanto; Fery Ramdani (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
Inventory of goods is an activity of recording goods as well as processing data on inventory of goods owned by a school. In educational institutions, school facilities and infrastructure are very important. Facilities and infrastructure are useful to support the implementation of the teaching and learning process, both directly and indirectly in an institution, to achieve educational goals. Good data management will provide great benefits for smoothness and success in the activities of an organization. Research with the title